Congestion control for named data networking-based wireless ad hoc network - Muchtar, Farkhana; Hamoud Al-Adhaileh, Mosleh; Alubady, Raaid; Kumar Singh, Pradeep; Ambar, Radzi; Stiawan, Deris (Springer Nature, 2020)
There is lack of complete congestion control solution that is optimized or practical with the Named Data Networking (NDN)-based MANET environment. All the existing suggested solutions are either for general NDN which is not optimized for MANET environment or congestion control solution for incomplete NDN-based MANET. Therefore, we recommend a complete congestion control solution speciﬁcally for NDN-based MANET which we call Standbyme Congestion Control or simply called Standbyme. Standbyme design optimized for NDN-based MANET needs in reducing network congestion’s bad effect such as goodput reduction, increment of number of packet loss or increment of delay in NDN-based MANET. Through the testbed experiment, we did by comparing Standbyme with other congestion control methods we selected for comparison, i.e., a practical congestion control for NDN (PCON) congestion control and best effort link reliability protocol (BELRP) congestion control, indicating Standbyme was able to drastically reduce network congestion in NDN-based MANET. Without sacriﬁcing the performance of NDN-based MANET, Standbyme has also reduced bad effect of network congestion through better approach of congestion prevention and reduction in MANET environment.